البرامج البینیة فى تعلیم المکتبات الرقمیة - د. سارة أحمد صالح (المجلة الدولية لعلوم المكتبات والمعلومات)
This study aims to study the most important features of Digital LibrariesEducation and topics which related to it, identifying the meaning of DLE its limitsfields and targets, Determine the scope of the formal Conceptual frameworks forDLE. Some of the most important results: DLE case took the attention ofspecialists since (1999) and till now .and since 2005 there were an increase inthe literature which informed this study, Many reports have stressed theimportance of incorporating interdisciplinary in DLE, The digital libraries mergedas a topic in different courses in (1990) but the concern of make separatecourses with title "Digital libraries" In (1996) and first cooperation effort inteaching digital libraries was in (1999- 2000). Based on the results obtained, theauthors contend that the future LIS education will consist of more of collaborativeprograms with several disciplines including CS, management, culture science,and so onto build an interdisciplinary Programs for Digital Library Education.